1985
DOI: 10.1111/j.1574-6968.1985.tb00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nikkomycin on chitin spine formation in the diatomThalassiosira fluviatilis, and observations on its peptide uptake

Abstract: The nucleoside antibiotic nikkomycin inhibited the formation of β‐chitin spines by the diatom Thalassiosira fluviatilis, and slowed its growth rate, at a minimum inhibitory concentration of 4 μM. The resulting chitin‐free cells sedimented much more rapidly in the cultures than did control cells. The uptake of nikkomycin was not antagonised by the dipeptides Gly‐Val, Met‐Met or Phe‐Leu. Of Six dipeptides tested, Met‐Met, Phe‐Leu and Tyr‐Gly were taken up by the diatoms, but Gly‐Gly, Gly‐Val and Ala‐Ala were not. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This is in accordance with previous studies performed by Gooday et al who observed that an inhibitory effect on chitin fiber formation is detectable for concentrations as low as 4 µM. 47 For this reason, we wanted to evaluate if the iminosugars (S,S)-32f, (R,S)-32e, (R,S)-32f, and (R,R)-33e influence the chitin fiber synthesis since iminosugars are well known to be inhibitors of glycosyltransferases in vitro. 19,22 In this assay the synthesized iminosugars were dissolved in DMSO and used in the reactions in a final concentration of 100 µM.…”
Section: Biological Evaluation Of Iminosugars With the Marine Diatom ...supporting
confidence: 94%
See 1 more Smart Citation
“…This is in accordance with previous studies performed by Gooday et al who observed that an inhibitory effect on chitin fiber formation is detectable for concentrations as low as 4 µM. 47 For this reason, we wanted to evaluate if the iminosugars (S,S)-32f, (R,S)-32e, (R,S)-32f, and (R,R)-33e influence the chitin fiber synthesis since iminosugars are well known to be inhibitors of glycosyltransferases in vitro. 19,22 In this assay the synthesized iminosugars were dissolved in DMSO and used in the reactions in a final concentration of 100 µM.…”
Section: Biological Evaluation Of Iminosugars With the Marine Diatom ...supporting
confidence: 94%
“…mollusks, fungi, and diatoms using micromolar concentrations of Nikkomycin Z, a dipeptide linked to a nucleoside chain first isolated from Streptomyces tendae . 44–47 Inhibitory effects were also observed with polyoxin D in marine diatoms. 46 A variety of mono- and bicyclic iminosugars, such as nojirimycin 1 , N -nonyl-1-deoxynojirimycin 2 , isofagomin 3 , pyrrolidine 4 and 7-desoxycasuarin 5 have been examined as CHS inhibitors in vitro (Scheme 1).…”
Section: Introductionmentioning
confidence: 91%